Seedling Production and Field Performance of Seedlings - Luoranen, Jaana (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Rapid establishment of seedlings in forest regeneration or afforestation sites after planting is a prerequisite for a successful reforestation. Seedling survival after outplanting can be improved by using high-quality seedling material. Seedling quality consists of several features, such as genetic source, morphological properties, nutritional status, stress resistance, and vitality of the seedlings. Field performance of the seedlings is a complex process which can be affected by many nursery and silvicultural practices. Nursery cultural practices strongly affect seedling quality, which is generally at its highest level during the growth period at the nursery. Afterwards, when the seedlings are transported from the nursery to the planting site (including seedling storage, handling, shipping, and planting practices), the quality of seedlings can only remain the same or decline. To ensure successful regeneration, it is important to produce seedlings that retain their high quality until planting, and to establish them quickly in the forest regeneration site.